PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN - Ibrahim, Malik; Thawil, Sitti Marijam (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
The purpose of this study is to determine the effect of product quality and service quality on customer satisfaction. The population in this study were 50 consumers who were taken by purposive technique. Multiple regression is used to test hypotheses. The results of the study showed that there was an effect of product quality and service quality significantly on customer satisfaction. The implications and suggestions are explained in the article. Keywords: Product Quality, Service Quality, Consumer Satisfaction.